2021
DOI: 10.1589/jpts.33.94
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxygen uptake adjusted by skeletal muscle mass in cardiovascular disease patients with type 2 diabetes

Abstract: We aimed to evaluate oxygen uptake adjusted by total skeletal muscle mass in patients with cardiovascular disease with or without type 2 diabetes mellitus. [Participants and Methods] The participants included 54 males ≥50 years of age without heart failure who underwent cardiopulmonary exercise testing during cardiac rehabilitation. We divided the participants into two groups: patients with type 2 diabetes mellitus (DM group) and patients without type 2 diabetes mellitus (NDM group). [Results] We found no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…The present results are consistent with the previous reports showing that CR patients with concomitant DM had significantly lower peak VO 2 than those without T2DM [ 25 ]. Nishihara et al have reported that the concurrent group with T2DM and cardiovascular disease showed 10.3% lower peak VO 2 than that of Non-DM cardiovascular disease patients [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…The present results are consistent with the previous reports showing that CR patients with concomitant DM had significantly lower peak VO 2 than those without T2DM [ 25 ]. Nishihara et al have reported that the concurrent group with T2DM and cardiovascular disease showed 10.3% lower peak VO 2 than that of Non-DM cardiovascular disease patients [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…This was in line with previous studies [26], in which patients with HbA1C > 7% were more likely to develop RV dysfunction, supporting the role of hyperglycemia on HF [27], with the known effects on microvascular dysfunction [28] and on coronary atherosclerosis [29]. T2D has been associated with lowered peak VO 2 in the general population [30,31] and HF patients [32]. Notably, recent studies showed that although there was no significant difference in peak cardiac output, peripheral extraction was lower in patients with T2D compared to controls.…”
Section: Baseline Echocardiographic and Cardiopulmonary Performance F...supporting
confidence: 90%
“…T2D has been associated with lowered peak VO 2 in the general population (24,25) and HF patients (26). Notably, recent studies showed that although there was no signi cant difference in peak cardiac output, peripheral extraction was lower in patients with T2D compared to controls.…”
Section: Baseline Echocardiographic and Cardiopulmonary Performance N...mentioning
confidence: 99%